1980
DOI: 10.1210/endo-107-6-1875
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Pulsatile Release of Growth Hormone in Old Male Rats*

Abstract: Pulsatile release of GH was compared in young (4-5 months old) and old (18-20 months old) male Sprague-Dawley rats using indwelling atrial cannulae. More than 57% of the young rats exhibited GH pulses greater than 300 ng/ml plasma, whereas only 7% of the old animals had GH pulses of similar amplitude. Trough GH values were not different between young and old rats, but during the 10.5-h sampling period, mean GH concentrations in young male rats were significantly greater than those in old male rats (175.3 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
122
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(138 citation statements)
references
References 0 publications
15
122
1
Order By: Relevance
“…Although it is generally accepted that basal GH secretion decreases in humans and animals with increasing age (Borst et al, 1994;De Genarro Colonna et al, 1994;Finkelstein et al, 1972;Sonntag et al, 1980;Wilshire et al, 1995;Zadik et al, 1985), the basal plasma GH concentration in our study was not significantly different in the young and the old dogs. For identifying age-related differences in GH secretion, determination of the pulsatile secretion pattern of GH is much more sensitive.…”
Section: Ghrp-6contrasting
confidence: 75%
“…Although it is generally accepted that basal GH secretion decreases in humans and animals with increasing age (Borst et al, 1994;De Genarro Colonna et al, 1994;Finkelstein et al, 1972;Sonntag et al, 1980;Wilshire et al, 1995;Zadik et al, 1985), the basal plasma GH concentration in our study was not significantly different in the young and the old dogs. For identifying age-related differences in GH secretion, determination of the pulsatile secretion pattern of GH is much more sensitive.…”
Section: Ghrp-6contrasting
confidence: 75%
“…In old male rats GH secretion is depressed, and this is associated with diminished pulsatile release of GH. The amplitude and duration of the pulses decrease, but the periodicity or number of pulses appears to be similar to that present in younger animals (9). That this decline in GH secretion of aging rats is due to aging and not to weight increase associated with aging was demonstrated in previous studies from our laboratory (10).…”
Section: Introductionmentioning
confidence: 50%
“…The mechanisms involved are unknown but may be due to alterations in the release of GRF and/or SRIF from the hypothalamus. For instance, a decrease in hypothalamic SRIF content has been noted in old rats (34). However, while injection of antiserum to SRIF in both young and old rats produces a similar increase of plasma GH in both age groups, a higher dose of antiserum causes an increase of plasma GH that is greater in the older than in the younger group (41).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that high-amplitude GH pulses in rats and humans, mean blood GH secretion in rats, and integrated GH values in humans diminish during aging (33)(34)(35)(36)(37)(38)(39)(40)(41). The mechanisms involved are unknown but may be due to alterations in the release of GRF and/or SRIF from the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%